Cholelithiasis in children: experience from Bangladesh - Gazi, MR (Mediscope, 2015)
Most of the time clinicians overlook the diagnosis of cholelthiasis in children because of its atypical presentation. The present study reports paediatric cases of cholelithiasis treated in Gazi Medical College Hospital, Khulna, Bangladesh during the period from 2002 to 2013. In order to assess the frequency of paediatric cholelithiasis cases and treatment outcome, the author reviewed the patient records. The retrospective analysis found 9 paediatric cases who underwent a laparoscopic cholecystectomy performed from 2002 to 2013 at Gazi Medical College Hospital by a single Consultant Surgeon (the author). The cases were 7 females and 2 males. The average age was 8 years. The reports and full case history notes were checked and data were extracted accordingly. Correspondence was done to confirm the outcome of any subsequent follow up. It was found that clinically no one was obese but nutritional deficiency was obvious because all the patients were from poor family. Final diagnosis was made by ultrasonography. All of them recovered uneventfully after laparoscopic cholecystectomy. Mediscope Vol. 2, No. 1: 2015, Pages 32-35